TEACHING STRATEGIES FOR MULTICULTURAL STUDENTS AT BIPAS, UDAYANA UNIVERSITY - Sri Rahayuni, Ni Ketut (Lingual Journal of Language and Culture, 2017)
The relationship between teacher and student involves not just instruction, but interaction. When interaction fails because of teacher misperceptions of student behavior, instructional failure will often follow. This is in line with teaching BIPAS students who come from different countries. Teachers should use certain teaching strategies in order to meet the students’ need and make the learning process successful. The aims of this research are to find out the teaching strategies and the situation of students-teacher interactions and students-students interactions in multicultural classrooms of BIPAS Program, Udayana University in Bahasa Indonesia classes. Malone (2012) stated that communicative approaches and instructional techniques are required to teach second language. The data was collected through a classroom observation and the documentation method through video recording during the classroom interaction was done to get the supporting data. It was found that communicative approach through emphasis on learning to communicative through classroom interaction, and cooperative learning such as small group discussion and pair work/discussion become the effective teaching strategies used for multicultural students at BIPAS, Udayana University. Both teacher -student interaction and student-student interaction are applied for multicultural students in the classroom. Keywords: multicultural students, teaching strategies, interaction, communicative approach